Pituitary adenomas: historical perspective, surgical management and future directions. (December 2015) - Theodros, Debebe; Patel, Mira; Ruzevick, Jacob; Lim, Michael; Bettegowda, Chetan
Pituitary adenomas are among the most common central nervous system tumors. They represent a diverse group of neoplasms that may or may not secrete hormones based on their cell of origin. Epidemiologic studies have documented the incidence of pituitary adenomas within the general population to be as high as 16.7%. A growing body of work has helped to elucidate the pathogenesis of these tumors. Each subtype has been shown to demonstrate unique cellular changes potentially leading to tumorigenesis. Surgical advancements over several decades have included microsurgery and the employment of the endoscope for surgical resection. These advancements increase the likelihood of gross-total resection and have resulted in decreased patient morbidity.